Influence of voltage deviation on the drive characteristics of working machines with dc motors of independent and parallel excitation at the torque of static supports linearly dependent on the angular velocity - Sinyavsky, O.; Savchenko, V.; Chmil, A.; Prudnikova, N. (Energy and Automation, 2026)
Studies on the influence of voltage deviation and asymmetry on the technological and energy characteristics of working machines and mechanisms with an asynchronous electric drive have shown that when they deviate, productivity decreases and specific energy consumption increases. However, there are no studies on the influence of voltage deviation on DC electric drives.The purpose of the study is to establish the influence of voltage deviation in electric drives with DC motors of independent and parallel excitation on the technological and energy characteristics of working machines with a static resistance moment that depends linearly on the angular velocity.When the voltage deviates, the angular velocity of DC motors of independent and parallel excitation changes, which causes a change in the productivity of the working machine. In DC motors of independent and parallel excitation with a saturated magnetic system, the dependence of the productivity of the working machine on the voltage change is linear.When the voltage deviates, the constant and variable power losses change in the DC electric motor.It is proposed to conduct an energy assessment of a DC electric drive based on specific electricity consumption.The study of the influence of voltage deviation on the energy characteristics of working machines with a static resistance moment linearly dependent on angular velocity, which are driven by DC motors of independent and parallel excitation, was carried out. It was established that when the voltage decreases, the specific electricity consumption decreases.Recieved 2025-12-12Recieved 2026-01-27Accepted 2026-02-11
Keywords: DC motor of independent and parallel excitation; voltage deviation; specific electricity consumption